IT POSSIBLE TO DECLARE A QUALIFIED PARDON UNFOUNDED? (Isagoge - Journal of Humanities and Social Sciences, 2025)
In this research we analyze the legal basis for the issuance of qualified pardons. The problem of the research is focused on the issuance of pardons in cases where the accused have a previous criminal record in their extract of filiation. For this purpose, we will proceed according to the following objectives. First, we will study the requirements of the pardon in the Chilean criminal system. Then, in the second section of this work, we will present the dogmatic foundations of pardon according to political parameters in qualified cases. In the third and fourth sections, we will focus on identifying the different alternatives to motivate a pardon decision. Finally, we will examine the use of principles in its dictation.  The expected results are to provide a strategy of rational argumentation in the dictation of qualified pardons that does not jeopardize the security of citizens, and the conclusion is that it is possible to use more than one principle in the dictation of pardons, such as the principles of security and human dignity.